PENGALAMAN SELF-CARE PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISA DIMASA PANDEMI COVID-19 - Erlyani, Suci Ayu; Simatupang, Lenny Lusia (Indonesian Trust Nursing Journal, 2023)
Chronic kidney failure is a progressive disorder, in which the ability of the kidneys in the body cannot recover to maintain metabolic, fluid and electrolyte balance, causing uremia. To maintain body functions, patients with chronic kidney failure perform kidney replacement therapy, which is one of the options. The purpose of this study is to explore the meaning of the patient's experience in undergoing hemodialysis during the Covid-19 pandemic. This research method is qualitative with a phenomenological method in which to explore the experience of self-care in each chronic kidney failure patient undergoing hemodialysis. The sample used by purposive sampling technique as many as 12 people. The data analysis technique used in this study is the Miles and Huberman method with three stages. The results of this study obtained three themes concerning Self-Care Experiences of Chronic Kidney Failure Patients Undergoing Hemodialysis During the Covid-19 Pandemic. The conclusions obtained in this study are: an overview of self-care of chronic kidney failure patients while undergoing hemodialysis, the efforts made by hemodialysis patients to prevent transmission of Covid-19, the expectations of hemodialysis patients for life. Abstrak Gagal ginjal kronis merupakan penyimpangan progresif, yang kemampuan ginjal dalam tubuh tidak bisa pulih untuk mempertahankan keseimbangan metabolik, cairan, serta elektrolit, sehingga menyebabkan uremia. Untuk mempertahankan fungsi tubuh penderita gagal ginjal kronis melakukan terapi pengganti ginjal yang menjadi salah satunya pilihan. Tujuan penelitian ini yaitu untuk menggali pengalaman pasien dalam menjalani hemodialisa selama pandemi covid-19. Metode penelitian ini yaitu kualitatif dengan metode fenomenologi untuk menggali pengalaman self care pada pasien gagal ginjal kronis yang menjalani hemodialisa. Adapun sampel yang digunakan dengan teknik purposive sampling sebanyak 12 orang. Teknik analisa data yang digunakan dalam penelitian ini, yaitu metode Miles dan Huberman dengan tiga tahap. Hasil penelitian ini mendapatkan tiga tema tentang Pengalaman Self-Care Pasien Gagal Ginjal Kronis Dalam Menjalani Hemodialisa Dimasa Pandemi Covid-19. Kesimpulan yang didapat dalam penelitian ini, yaitu : gambaran perawatan diri pasien gagal ginjal kronis saat menjalani hemodialisa, upaya yang dilakukan pasien hemodialisa untuk mencegah penularan covid-19, harapan pasien hemodialisa terhadap kehidupan.